2013
DOI: 10.1242/jcs.118943
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of TRPC1–STIM1 channel assembly and AQP5 translocation compromise agonist-stimulated fluid secretion in mice lacking caveolin1

Abstract: SummaryNeurotransmitter regulation of salivary fluid secretion is mediated by activation of Ca 2+ influx. The Ca 2+ -permeable transient receptor potential canonical 1 (TRPC1) channel is crucial for fluid secretion. However, the mechanism(s) involved in channel assembly and regulation are not completely understood. We report that Caveolin1 (Cav1) is essential for the assembly of functional TRPC1 channels in salivary glands (SG) in vivo and thus regulates fluid secretion. In Cav1 2/2 mouse SG, agonist-stimulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
41
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 54 publications
(81 reference statements)
7
41
0
Order By: Relevance
“…Caveolin-1 can contribute to assembly of store-operated Ca 21 influx channels by regulating plasma membrane localization of TRPC1 in the caveolae compartment (41)(42)(43). Recent studies have further indicated that caveolin-1 not only directly interacts with TRPC1 (44,45), but also participates in the membrane localization and the cluster interaction of the main SOCC molecules, TRPC stromal interaction molecule (STIM)-ORAI calcium release activated calcium modulator (ORAI), upon intracellular calcium store depletion and the intracellular calcium sensor stromal interaction molecule 1 (STIM1) translocation, which is believed to be a key event during intracellular calcium mobilization (46).…”
Section: Discussionmentioning
confidence: 99%
“…Caveolin-1 can contribute to assembly of store-operated Ca 21 influx channels by regulating plasma membrane localization of TRPC1 in the caveolae compartment (41)(42)(43). Recent studies have further indicated that caveolin-1 not only directly interacts with TRPC1 (44,45), but also participates in the membrane localization and the cluster interaction of the main SOCC molecules, TRPC stromal interaction molecule (STIM)-ORAI calcium release activated calcium modulator (ORAI), upon intracellular calcium store depletion and the intracellular calcium sensor stromal interaction molecule 1 (STIM1) translocation, which is believed to be a key event during intracellular calcium mobilization (46).…”
Section: Discussionmentioning
confidence: 99%
“…AQP5 is known to be present in parotid gland exosomes [13,14], which accumulate within multivesicular bodies and are released into saliva from parotid cells upon fusion of multivesicular bodies with the plasma membrane in a Ca 2+ -triggered reaction [15,16]. In salivary glands, the Ca 2+ -permeable transient receptor potential canonical 1 (TRPC1) plays an important role in the agonist-induced increase in [Ca 2+ ]i [2,17]. AQP5 was also demonstrated to be rapidly translocated from the cytoplasm to the APM by enhancement of [Ca 2+ ]i during sweating in sweat glands [18].…”
Section: Introductionmentioning
confidence: 99%
“…The CRAC-activating domain of STIM1 is necessary for the interaction with TRPC, whereas its C-terminal cationic lysine-rich region is necessary for TRPC activation (50 -53). This TRPC-STIM1 cooperation plays a role in physiological functions such as fluid secretion in salivary glands (54), postnatal differentiation of human myoblasts (36), and disruption of the endothelial barrier (35). STIM2 protein has been less studied than STIM1.…”
mentioning
confidence: 99%